2015
DOI: 10.3109/01443615.2015.1041885
|View full text |Cite
|
Sign up to set email alerts
|

Single-port access total laparoscopic hysterectomy with Korean-made OCTO Port: Turkish surgeons’ initial experience

Abstract: We present our initial experience with single-port access total laparoscopic hysterectomy (TLH) surgery using a Korean-made laparoscopic port (OCTO™ Port). In a retrospective study, single-port access TLH (SPA-TLH) with the OCTO Port was performed on 34 patients with benign gynaecological indications from July 2013 to May 2014 by two surgeons (Ahmet Kale and Hasan Terzi). All patients were divided into two groups. The first 15 patients who underwent SPA-TLH were classified as Group 1, and the second 19 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…All procedures were performed by the same surgical team according to a previously described technique. 6 The details of procedures are summarized next.…”
Section: New Turkish-made Laparoscopic Needle Holdermentioning
confidence: 99%
“…All procedures were performed by the same surgical team according to a previously described technique. 6 The details of procedures are summarized next.…”
Section: New Turkish-made Laparoscopic Needle Holdermentioning
confidence: 99%
“…In one of these studies, LESS-TH was performed in endometrial cancer cases. 3,7,13,[15][16][17][18] In another study, the same procedure was used for the treatment of benign and malignant uterine pathologies. Jung et al reported that the mean operation time was 89 min.…”
Section: Less-th Tlh (N=22) (N=47)mentioning
confidence: 99%
“…Recently, innovations in the technology such as multi-channel single-port, articulating instruments, and flexible endoscopes have allowed laparoscopic surgeons to perform increasingly complex gynecological and gynecologic-oncologic operations. [2][3][4][5][6][7] A recent systematic review by Mencaglia et al identified 65 studies (17 case reports, 32 cases studies, 13 retrospective comparative studies and three randomized clinical trials) and reported that LESS is safe and feasible for most benign gynecologic surgeries. 8 A randomized clinical trial that evaluated LESS compared to conventional laparoscopic-assisted vaginal hysterectomy reported significant decreases in post-operative pain and analgesic use in the LESS-assisted vaginal hysterectomy group.…”
mentioning
confidence: 99%
See 1 more Smart Citation